PERTANGGUNGJAWABAN PIDANA ANAK PELAKU TINDAK PIDANA NARKOTIKA BERBASIS KEADILAN RESTORATIF - Sekha Anggita Maulidina; Irwan; Mulyana, Aji (Universitas Kapuas, 2025)
The increasing involvement of children in narcotics abuse in Indonesia poses significant challenges for juvenile justice and child protection systems. This study examines the criminal responsibility of child offenders from a restorative justice perspective, focusing on the implementation of diversion and rehabilitative approaches. Using normative legal research and analysis of legislation, case studies, and court decisions, particularly case No. 53/Pid.Sus.Anak/2017/PN.Jkt.Brt, the research highlights the gap between progressive laws and their practical application. Findings reveal inconsistent diversion efforts and limited rehabilitation support, resulting in punitive rather than restorative treatment of child offenders. The study concludes that comprehensive reform is necessary to ensure a juvenile justice system that prioritizes the best interests and future well-being of children involved in narcotics offenses.